3D Printing: Opportunities, Risks and Regulation (Revista Paradigma, 2022)
This article studies opportunities and risks arising from the use of 3D printers, mainly in relation to Law. Its hypothesis is that governments need to adapt to the socioeconomic transformations that 3D printing technology generates, filling gaps that their current regulations have, through the insertion of ethical principles for the protection of people's safety for the regulation of such technologies. As a result, there are: i) the growing presence of 3D printing technologies in society, which may impact consumption and production relationships, placing the possibility of manufacturing products of the most varied types in the hands of consumers; ii) applications such as printing of food and living tissue offer answers to several needs currently faced; iii) 3D printing generates risks and uncertainties regarding its use in the arms market, regarding violations of Intellectual and Industrial Property Rights, as well as consumer protection, and as a result, legal systems around the world must receive important aspects from 3D printing to its regulation, filling gaps in its orders. Methodology: hypothetical-deductive procedure method, qualitative approach and bibliographic-documentary technique.